2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.25464
|View full text |Cite
|
Sign up to set email alerts
|

Homework Methods in Engineering Mechanics, Part Two

Abstract: University of South Florida in 2012. He is committed to developing his courses to apply and develop best practices from the scholarship of teaching and learning. Outside of course development, his primary research interests are in biomechanics, rehabilitation, prosthetics, and robotics. His current research projects include robotic methods modeling and predicting human motion, the functional evaluation of a variety of prosthetic devices, and the creating of low-cost virtual reality systems for stroke rehabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…With many schools turning towards online homework systems as a method for assigning homework and assessing students, it is worth asking the students if they value it, and if they value it with respect to how it is being used. Certainly, there is literature backing both sides of the coin; for and against, online systems and traditional homework methods [3], [4], [7]- [9], [11]. Students however, are clearly asking for both, and indicate that both will probably be helpful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With many schools turning towards online homework systems as a method for assigning homework and assessing students, it is worth asking the students if they value it, and if they value it with respect to how it is being used. Certainly, there is literature backing both sides of the coin; for and against, online systems and traditional homework methods [3], [4], [7]- [9], [11]. Students however, are clearly asking for both, and indicate that both will probably be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a lot of work assessing and analyzing the correlation between student performance on online homework assignments and exams [4]- [7]. A longitudinal study shows online homework leads to better student performance [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far we have concluded that the use of traditional hand-written homework, frequent assessment via quizzes [1], or the Pearson Mastering Engineering [2] software for formative assessment did not have a significant impact on students' performance on exams. It was also observed that neither traditional nor online homework scores correlated well with exam scores, however in-class quizzes did correlate with final exam scores.…”
Section: Introductionmentioning
confidence: 87%
“…Over the current and previous study [1,2] durations, data from 12 sections of an Engineering Mechanics (Statics and Dynamics) course, over a period of 3 years were collected. Data were taken from one section of Fall 2013, and Spring 2014, and two sections each from Fall 2014, Spring 2015, Fall 2015, Spring 2016, and Fall 2016.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation